2016
DOI: 10.1016/j.actamat.2015.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Topologically close-packed phases: Deposition and formation mechanism of metastable β-W in thin films

Abstract: β-W is a metastable, topologically close-packed phase with the A15 structure. The deposition of β-W, using N 2 as the impurity gas introduced into the sputtering chamber, is reported and a mechanism for its formation is proposed. Molecules of the impurity gas in the chamber are adsorbed onto the surface during the deposition process and act as nucleation sites for the formation of β-W. The proposed mechanism is supported by the dependence of β-W phase fraction in sputter deposited films on pressure of N 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…Prior work had shown that the introduction of nitrogen during sputter deposition of tungsten promotes the formation of -W phase. 15 The N 2 pressure was calibrated in the absence of Ar by filling the load-lock chamber to a given pressure and determining the nitrogen pressure in the deposition chamber at the steady-state leak rate through the gate valve separating the deposition chamber from the load-lock chamber. The N 2 pressure in the deposition chamber was 1.2 ⇥ 10 5 Torr for the current study.…”
Section: A Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work had shown that the introduction of nitrogen during sputter deposition of tungsten promotes the formation of -W phase. 15 The N 2 pressure was calibrated in the absence of Ar by filling the load-lock chamber to a given pressure and determining the nitrogen pressure in the deposition chamber at the steady-state leak rate through the gate valve separating the deposition chamber from the load-lock chamber. The N 2 pressure in the deposition chamber was 1.2 ⇥ 10 5 Torr for the current study.…”
Section: A Experimentsmentioning
confidence: 99%
“…The N 2 pressure in the deposition chamber was 1.2 ⇥ 10 5 Torr for the current study. 15 Following the deposition of the trilayer stack of Cu/SiO 2 / -W and prior to lift-off to generate free-standing films for DSC measurements, the films were examined by ✓-2✓ X-ray diffraction (XRD) scans. The scans were done out-of-plane, i.e., with the scattering vector normal to the film plane, using a Rigaku Ultima III diffractometer at the Center for Functional Nanomaterials at Brookhaven National Laboratory.…”
Section: A Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For preparation of β‐W films, it is a simple procedure for both magnetron sputtering and chemical vapor deposition (CVD) . During deposition, impurities, such as oxygen, nitrogen, carbon, silicon, and germanium from environment or reaction atmosphere, are generally beneficial for preferred nucleation and growth of metastable β phase. However, in situ substrate heating (>300 °C) is indispensable to attain α‐W films based on CVD methods .…”
Section: Introductionmentioning
confidence: 99%
“…TCP phases are of particular interest in high-performance materials such a Ni-base superalloys [27] as their formation significantly influences the materials properties [28]. In tungsten, the transformation between the A15 and bcc phase has recently attracted increased attention [29,30] since for applica-arXiv:1905.01536v1 [cond-mat.mtrl-sci]…”
mentioning
confidence: 99%